SARS-CoV-2 infection and pregnancy: clinical update and perspective - Wang, Chen; Yang, Huixia (Chinese medical journal, 2023)
Since the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in December 2019, the virus has overwhelmed the world's health. A meta-analysis including 42 studies involving 438,548 pregnant women with comparison data on evaluating disease severity and perinatal outcomes indicated that compared with no SARS-CoV-2 infection in pregnancy, SARS-CoV-2 infection in pregnancy was associated with 33%, 82%, and 2-fold increased risk of preeclampsia (PE), preterm birth (PTB), and stillbirth, respectively. [...]compared with mild SARS-CoV-2 infection, severe SARS-CoV-2 infection was strongly associated with PE, PTB, gestational diabetes, and low birth weight; and the odds ratio reached as high as 4.16, 4.29, 1.99, and 1.89, respectively. [23] Pregnant and breastfeeding women are vulnerable populations to mental health disorders. In the context of the pandemic, maternal psychological problems might be further exacerbated by limited social support, social isolation, change in routine associated with SARS-CoV-2 infection, and especially concerns and fears regarding the risk of morbidity and mortality associated with SARS-CoV-2 infection for themselves, their fetus, or their newborn infants. [...]attention should be paid to perinatal mental health during pandemic and timely intervention should be carried out to relieve psychological problems and support the health of both mothers and children.